Correctional Officers in Canada: Interpreting Workplace Violence. (December 2018) - Ricciardelli, Rose; Power, Nicole; Medeiros, Daniella Simas
The potential for violence in prison shapes how correctional officers (COs) carry out their work. Yet, how provincial COs experience violence remains understudied. Using theoretical insights from the literature on workplace violence in caring and service occupations, we analyze observational data and interviews conducted with COs in eastern Canada. We show that COs carry out their everyday work under increasingly strained conditions (e.g., understaffing) and manage prisoners' (sometimes violent) responses to deteriorating prison conditions (e.g., overcrowding) by engaging in emotional labor. The COs understand workplace violence as an inevitable "part of the job, " which serves to normalize the experience of workplace violence and deflect attention away from the prison conditions which exacerbate and even produce violence.